Dual Drug Loaded Nanotheranostic Platforms as a Novel Synergistic Approach to Improve Pancreatic Cancer Treatment. (23rd February 2023) - Barui, Sugata; Conte, Marzia; Percivalle, Nicolò Maria; Montero, Rocío María García; Racca, Luisa; Allione, Marco; Cauda, Valentina
Abstract: This study focuses on the development of theranostic, dual drug‐loaded nanocarriers to propose a proof‐of‐principle therapeutic approach in the treatment of pancreatic ductal adenocarcinoma (PDAC). The nanoconstructs consist of a core of zinc oxide nanocrystals doped with gadolinium, useful as a potential contrast agent in magnetic resonance imaging applications. After functionalizing their surface with amino‐propyl groups, the physical adsorption of two hydrophobic drugs is performed: Vismodegib and Sorafenib. Their synergistic use might improve PDAC treatment and stroma depletion when co‐delivered in the tumor microenvironment for future in vivo applications. To enhance the nanoconstructs' biostability, the ensemble is coated by a lipid bilayer and a tumor targeting peptide is incorporated on the outer shell surface. As a first proof of concept, the resulting nanoconstructs are tested against two pancreatic cancer cell lines, showing a modest increase in treatment efficacy compared to the free drug counterparts and proving to spare healthy pancreatic cells. In a second testing set, the dual‐drug loaded nanoconstructs are tested on both cell lines previously sensitized to a first‐line chemotherapeutic drug, Gemcitabine, showing an improved treatment response. From these preliminary results, the nanotheranostic platforms might constitute a good starting point for future PDAC therapy and diagnosis studies. Abstract : This study aims at proposing a first proof‐of‐concept of a theranostic, biomimetic, targeted, and dual drug loaded zinc oxide‐based platform meant to provide a new therapeutic approach against pancreatic ductal carcinoma and tested on two pancreatic cancer cells in terms of preliminary treatment efficacy. The promising results presented pave the way for further in vitro and in vivo applications.